How to achieve entrepreneurial enterprise performance in entrepreneurial scenario? – Based on the case study of China new energy passenger car company A - Dai, Jianxin; Lu, Xiaowei; Qi, Huibo; Zhang, Bo; Wang, Wei (Frontiers in Psychology, 2022)
This research is based on a Chinese new energy automobile startup enterprise. On the basis of the development process from 2014 to 2021, this research uses entrepreneurial scenario and entrepreneurial performance theory, and adopts exploratory case study methods to study entrepreneurial enterprise performance, focusing on the two themes of "what to do" and "how to do". The study found that, in China's entrepreneurial context, cultural context has the most significant impact on entrepreneurial enterprise performance. The accurate prediction of institutional scenarios by entrepreneurial enterprises can improve enterprise performance, while economic scenarios negatively stimulate entrepreneurial enterprise performance. This study shows that in the development process of entrepreneurial enterprises based on China's entrepreneurial scenario, the governance style and strategic choice of entrepreneurial enterprises should match the scenarios at different stages. In different stages of development, entrepreneurial enterprises should flexibly adapt to entrepreneurial scenarios and adopt different strategies to reflect their advantages in entrepreneurial scenarios and improve the success rate of entrepreneurship.